Pengenalan Huruf Hijaiyah Melalui Metode Ummi di TK Kreatif Al-Furqon - Khoirotun Ni'mah, Isnaini; Roziqin, Achmad (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The Ummi method is a method for reading the Al-Quran which focuses on 3 qualities, namely a quality method, a quality teacher and a quality system. The introduction of hijaiyah letters is one of the elements in this method. This research aims to determine the application of the Ummi method in introducing hijaiyah letters to students at the TK Kreatif Al-Furqon. This research uses a qualitative method with 3 data collection techniques, namely interviews, observation and documentation. The results of this research are that the introduction of hijaiyah letters using the Ummi method at the TK Kreatif Al-Furqon is going well as seen from the students' ability to read volumes in accordance with TK Kreatif Al-Furqon target, namely a maximum of volume 3.